A damage plasticity model for different types of intact rock. (December 2015) - Unteregger, D.; Fuchs, B.; Hofstetter, G.
Abstract: A constitutive model for describing the nonlinear mechanical behavior of different types of intact rock subjected to complex 3D stress states is presented. It is formulated on the basis of a combination of plasticity theory and the theory of damage mechanics along the lines of a damage-plastic model for concrete. Irreversible deformations, associated with strain hardening and strain softening, as well as degradation of stiffness can be modeled. The material parameters and the model parameters are identified by means of an optimization procedure combining an evolutionary and gradient based optimization algorithm with niching strategy. The proposed model is validated by numerical simulations of laboratory experiments conducted on specimens of marble, granite and sandstone. The simulations are performed at integration point level. Thereby, the capability of capturing key features of the constitutive behavior of different types of intact rock is demonstrated. Finally, the application of the model to structural analyses is demonstrated by simulating a boundary value problem, including the formation of shear bands. Abstract : Highlights: An advanced damage plasticity model for different types of intact rock is proposed. Strain hardening and strain softening as well as degradation of stiffness are modeled. A parameter identification scheme adopting an optimization algorithm is presented. The stress–strain behavior of different types of intact rock can be captured very well. The capability to handle shear banding is shown by FE-analyses of biaxial tests.